Strategies For Improving The Sharia Financial Literacy Index In The Millenial Generation In Indonesia - Abdul Rachman; Nathan Putra Kartaatmadja; Zulfa Ananta Rasya; Siti Husniyyah (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2022)
This study aims to analyze the Islamic financial literacy index and strategies to increase the Islamic financial literacy index in the millennial generation because based on data released by the OJK through the 2019 National Financial Literacy and Inclusion Survey that the level of Islamic financial literacy is relatively low at 8.39%. The methodology in this study is to use qualitative research with a library approach by analyzing the results of a survey conducted by OJK relating to Islamic financial literacy. The results of this study explain that the Islamic financial literacy index for the millennial generation is low so several strategies are needed to increase the Islamic financial literacy index, namely strategies to educate and socialize the importance of Islamic finance in financial management for millennials through social media, strategies for government participation in increasing Islamic financial literacy, strategies for collaboration between the government and educational institutions in providing easy access to Islamic finance with programs for the millennial generation, strategies for utilizing influencer marketing in marketing Islamic banking products and services, and strategies for increasing the Islamic financial literacy index through the participation of Islamic financial institutions by providing rewards for the millennial generation who have utilized sharia financial products and services.